2018
DOI: 10.1038/s41396-018-0100-6
|View full text |Cite
|
Sign up to set email alerts
|

Population genomic analysis of the rice blast fungus reveals specific events associated with expansion of three main clades

Abstract: We examined the genomes of 100 isolates of Magnaporthe oryzae (Pyricularia oryzae), the causal agent of rice blast disease. We grouped current field populations of M. oryzae into three major globally distributed groups. A genetically diverse group, clade 1, which may represent a group of closely related lineages, contains isolates of both mating types. Two well-separated clades, clades 2 and 3, appear to have arisen as clonal lineages distinct from the genetically diverse clade. Examination of genes involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
108
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(123 citation statements)
references
References 74 publications
15
108
0
Order By: Relevance
“…(N=43) [30] and Zhong et al . (N=88) [31] . The combined use of samples from these two studies increases not only the number of M. oryzae samples but also their geographical spread (Supp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(N=43) [30] and Zhong et al . (N=88) [31] . The combined use of samples from these two studies increases not only the number of M. oryzae samples but also their geographical spread (Supp.…”
Section: Resultsmentioning
confidence: 99%
“…Zhong et al . [31] divided their dataset in three groups (I-III) but did not identify group IV, since their dataset only include one individual from this group. In addition to groups I-IV, Gladieux et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Records of rice blast disease in China date back to the early 17 th century and until today it is recognized as one of the most threatening and widely distributed rice diseases [39]. Recent population genetics studies revealed that the rice-infecting lineage of M. oryzae consists of both a recombining population and multiple, clonally expanded lineages [42][43][44]. In Europe, the rice blast fungus population consists of only one of three major clonal lineages and it is possible that mating type isolation led to local asexual expansions.…”
Section: Introductionmentioning
confidence: 99%